Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1201/b12322-41
|View full text |Cite
|
Sign up to set email alerts
|

Kitting as an information source in manual assembly

Abstract: In manual assembly, a strategy to meet the goal of efficient production is the increased use of kitting as a material supply principle. Even though kitting is already implemented in industry, there are still uncertainties regarding the effects of introducing kits, particularly from a human factors perspective. This paper presents initial steps in the development of a method to be used for the evaluation of kitting. This from an information source point of view and for studying effects related to productivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…From previous studies (Brolin, Bäckstrand, Thorvald, Högberg, & Case, 2012;Hanson & Brolin, 2013), areas concerning manufacturing and human performance were considered more interesting, compared to other investigated research areas included in the abovementioned studies, e.g. logistics.…”
Section: Exploration Studies Leading To Hypotheses Of Experimental Studymentioning
confidence: 99%
See 3 more Smart Citations
“…From previous studies (Brolin, Bäckstrand, Thorvald, Högberg, & Case, 2012;Hanson & Brolin, 2013), areas concerning manufacturing and human performance were considered more interesting, compared to other investigated research areas included in the abovementioned studies, e.g. logistics.…”
Section: Exploration Studies Leading To Hypotheses Of Experimental Studymentioning
confidence: 99%
“…A lot of information is usually also displayed in a small area, making it difficult for the reader to quickly distinguish, extract and interpret specific information which often is the case in the automotive industry. A previous investigation (Brolin et al, 2012) showed that the most common information the assembler is in need of concerns the type of product variant, and thus what components to pick and assemble.…”
Section: How To Present Information -Syntaxmentioning
confidence: 99%
See 2 more Smart Citations
“…Such situations lead to varying quality in the instructions. Despite the vast amount of publications about information presentation, see Brolin et al (2012), Fässberg et al (2012, Ganier (2004), Ganier and de Vries (2016), Mattsson, Fast-Berglund and Li (2016) Schuh, Franzkoch, Prote, Luckert, Sauermann and Basse (2017, Syberfeldt et al (2016), Thorvald et al (2010) and Watson et al (2010), the designs and presentations of the assembly work instructions do not only vary among the case companies, but also within one company. In previous case studies ( Johansson, Delin, Jansson, Moestam and Fast-Berglund, 2016;Johansson et al, 2017), both paper-based assembly work instructions and digital instructions are used in different parts of the global production network whose assembly information originates from different IS.…”
Section: Assembly Work Instructionsmentioning
confidence: 99%